Evaluation of electrochemical properties for water splitting by NiO nano-cubes synthesized using Olea ferruginea Royle. (August 2020) - Zahra, Taghazal; Ahmad, Khuram Shahzad; Zequine, Camila; Gupta, Ram K.; Guy Thomas, Andrew; Azad Malik, Mohammad
Abstract: Low-cost and efficient electro-catalysts can play a key role in electro-catalytic water oxidation reaction. Hereinto, highly stable semiconducting nickel oxide (NiO) nanoparticles were synthesized by a facile, biomimetic and cost effective one pot synthesis route. Nickel (II) acetate tetrahydrate was used as a precursor and medicinal plant Olea ferruginea Royle as a reducing agent. The biosynthesized NiO NPs were scrutinized by UV–Vis absorption spectroscopy UV Vis.), Fourier transform infrared spectroscopy (FTIR), gas chromatography mass spectroscopy (GC–MS), X-ray diffractometer (XRD), energy dispersive X-ray spectrometer (EDX), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The average particle size of the NiO NPs was 13 ± 1 nm which was calculated by Scherrer equation, with uniform cubic shape. NiO supported on Ni-foam was investigated as an electro-catalyst for water splitting application. The results revealed an over potential of 0.41 V and Tafel slope of 97 mVdec −1 at 10 mA/cm 2 which is comparable to benchmark catalysts. These results suggests that the organic framework derived NiO could be a competitor to the chemically synthesized electrode material that comprises of costly reagents and require advanced synthesis approaches. Thus, in present study we believe that bio-assisted NiO is an efficient electrode material for water splitting studies and could be a sustainable step towards the replacement of noble metal-based electro-catalysts for energy conversion.